The Role of South-South FDI in the Economies of Developing Asia - Robert E. Lipsey; Fredrik Sjöholm (Asian Development Bank (ADB), 2011)
This paper attempts to measure the size of South–South foreign direct investment (FDI) in developing East Asia and the trends in it, and the characteristics of the investing countries and the investments themselves. It also summarizes the findings of studies in individual countries of the effects of these investments. The studies of individual countries will be used to try to find some consensus on differences between South–South FDI and North–South FDI. Among the comparisons of the two types of FDI we try to summarize are findings about their industrial composition; their effects on their host countries; and their host-country firms' productivity, wages, and employment, and explore how these differ across industries. Our analysis shows that the increased presence of South FDI in East and Southeast Asia might have different effects on host economies from those of FDI from the North.
hdl:11540/2010
Keywords: 330; Auslandsinvestition; Süd-Süd-Beziehungen; Asien